2021
DOI: 10.1177/00031224211011981
|View full text |Cite
|
Sign up to set email alerts
|

How Legacies of Geopolitical Trauma Shape Popular Nationalism Today

Abstract: Geopolitical competition and conflict play a central role in canonical accounts of the emergence of nation-states and national identities. Yet work in this tradition has paid little attention to variation in everyday, popular understandings of nationhood. We propose a macro-historical argument to explain cross-national variation in the types of popular nationalism expressed at the individual level. Our analysis builds on recent advances on the measurement of popular nationalism and a recently introduced geopol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 95 publications
(135 reference statements)
1
19
0
Order By: Relevance
“…Additionally, effects of single dimensions on attitudes cannot be differentiated. In fact, previous results show that two of the inductively identified types of national identity show “striking similarities in demographic profiles” (Bonikowski & DiMaggio, 2016, p. 17), similar effects on especially anti‐migration attitudes (Bonikowski & DiMaggio, 2016), similar prevalence in geopolitically challenged states (Soehl & Karim, 2021), and even strikingly similar profiles of membership criteria (cf. Bonikowski, 2016, p. 19; cf.…”
Section: The Missing Conceptual–methodological Link In National Ident...mentioning
confidence: 92%
See 1 more Smart Citation
“…Additionally, effects of single dimensions on attitudes cannot be differentiated. In fact, previous results show that two of the inductively identified types of national identity show “striking similarities in demographic profiles” (Bonikowski & DiMaggio, 2016, p. 17), similar effects on especially anti‐migration attitudes (Bonikowski & DiMaggio, 2016), similar prevalence in geopolitically challenged states (Soehl & Karim, 2021), and even strikingly similar profiles of membership criteria (cf. Bonikowski, 2016, p. 19; cf.…”
Section: The Missing Conceptual–methodological Link In National Ident...mentioning
confidence: 92%
“…Bonikowski & DiMaggio, 2016, p. 11; cf. Soehl & Karim, 2021, p. 10). Therefore, the way membership criteria are employed may be the driving force in explaining antimigrant attitudes.…”
Section: The Missing Conceptual–methodological Link In National Ident...mentioning
confidence: 99%
“…A similar relationship has been evidenced by Hjerm and Schnabel (2010: 535), whose study shows that a strong presence of armed conflicts in collective memory is related with stronger national sentiments, including the view that a given country should pursue its own interests regardless of the cost. What is more, the latest line of research shows that the experience of “geopolitical trauma” by a country, namely threats to its integrity and losses of its territory in the past, is linked with prevalence of more restrictive visions of nation among its citizens (Soehl and Karim, 2021). This can explain higher scores on items measuring ethno-racial type of national identity among fans of Polish football clubs, as such trauma is repeatedly reminded in ultras’ performances in the stadiums.…”
Section: Discussionmentioning
confidence: 99%
“…They used US survey data and an advanced statistical technique (latent class analysis, which I will discuss later) to identify four distinct clusters of responses to multiple survey questions about nationalist beliefs, which they attributed to four types of American national identities. In subsequent research, studies have shown that in the past two decades, the overlap between particular nationalism types and political party identification has increased in the United States (Bonikowski, Feinstein and Bock 2021), that Bonikwoski and DiMaggio's typology of nationalism may apply to other countries (Bonikowski 2017), and that cross-national differences in the prevalence of particular types of nationalism (i.e., some more defensive and exclusionary than others) can be attributed to differences in nations' past experiences of geopolitical competition and threat (Soehl and Karim 2021). Crucially, because an individual's nationalism type is linked to political attitudes and policy preferences, sorting the population into distinct nationalism types helps explain intranational variation in political attitudes and policy preferences (Bonikowski, Feinstein and Bock 2021).…”
Section: National Beliefs That Affect Meaning-makingmentioning
confidence: 99%